Visible photoluminescence of color centers in LiF crystals for absorbed dose evaluation in clinical dosimetry. Issue 1 (March 2015) - Villarreal-Barajas, J E; Piccinini, M; Vincenti, M A; Bonfigli, F; Khan, R F; Montereali, R M
Abstract: Among insulating materials, lithium fluoride (LiF) has been successfully used as ionizing radiation dosemeter for more than 60 years. Thermoluminescence (TL) has been the most commonly used reading technique to evaluate the absorbed dose. Lately, optically stimulated luminescence (OSL) of visible emitting color centers (CCs) has also been explored in pure and doped LiF. This work focuses on the experimental behaviour of nominally pure LiF crystals dosemeters for 6 MV x rays at low doses based on photoluminescence (PL) of radiation induced CCs. Polished LiF crystals were irradiated using 6 MV x rays produced by a clinical linear accelerator. The doses (absorbed dose to water) covered the 1-100 Gy range. Optical absorption spectra show stable formation of primary F defects up to a maximum concentration of 2×10 16 cm −3, while no significant M absorption band at around 450 nm was detected. On the other hand, under Argon laser excitation at 458 nm, PL spectra of the irradiated LiF crystals clearly exhibited the characteristic F2 and F + 3 visible broad emission bands. Their sum intensity is linearly proportional to the absorbed dose in the investigated range. PL integrated intensity was also measured using a conventional fluorescence optical microscope under blue lamp illumination. The relationship between the absorbed dose and the integrated F2 and F + 3 PL intensities, represented by the net average pixel number in the optical fluorescence images, is also fairly linear. Even at the low point defect densities obtained at the investigated doses, these preliminary experimental results are encouraging for further investigation of CCs PL in LiF crystals for clinical dosimetry.